PENGARUH MODEL PEMBELAJARANSEARCH SOLVE CREATE SHARE(SSCS) TERHADAP KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA SISWA KELAS VIII SMPN 14 KOTA PEKANBARU TAHUN PELAJARAN 2014/2015 (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The objective of mathematical studies is basically for the students to be able to utilize or apply math that they learned in everyday life and in learning other subjects. The results of studentâs math learning could be observed from their ability to solve math problems consisting of equation and narrative problems. Narrative problems are questions which are presented in a story-like manner and have relations with the situation that the students face in everyday life. Mathematics is one of the least favored subject and the studentâs mastery over the subject are quite lacking, also the difficulty of students to solve such narrative problems. As such, there is a need to exercise this research to increase the studentsâ capability in solving narrative problems. This research aims to discover (1) Toobserve the SSCS learning implementation model by mathematic teachers in class. (2) To discover the effect of SSCS learning model towards the ability to solve mathematical narrative problems to VIII grade students of National Middle School 14 Pekanbaru academic years 2014/2015. The research design that was used is Quasi Experimental. The experiment design that is going to be used in this research is The One Group Pretest-posttest Design which includes Quasi Experimental Design Without Control Group with the sample of 28 students of the VIII grade National Middle School 14 Pekanbaru. Data collection is done through observation and learning test results.The result of this research shows that (1) The SSCS Learning Implementation Model in National Middle School 14 Pekanbaru had been done according to the Learning Implementation Plan. (2) There is a significant influence from the SSCS learning model towards the studentsâ capability in solving narrative problems, in which this case could be seen from the average score after treatment is better than before. Meanwhile, the behavior and skills of the students have not all reached the required Mastery Minimum Criteria. There are still 5 more students that have not yet reached the Mastery Minimum Criteria in terms of behavior and 6 more in terms of skills.Key words: Influence, Narrative Problem, SSCS Learning, Capability, Solve